The key to system performance lies in implementation: Empirical evidence from labor dispute data of Shanghai from 1918 to 1940 - Junjie Honga; Zhihua Guan (Journal of Applied Economics, 2021)
The process of system implementation could be the key to determining system performance. This paper discusses this issue by using empirical methods to analyze Shanghai labor dispute cases. Although the labor dispute settlement system is designed to protect workers, empirical analyses show that government intervention will inhibit workers in labor disputes. Further analysis reveals that government intervention is selective based on the case reasons and differs in intensity. In addition, the events that affect government power may influence the case outcome.
Keywords: 330; System performance; system implementation; labor dispute mediation